Cognitive Remediation: A New Generation of Psychosocial Interventions for People with Schizophrenia. - Eack, Shaun M. (Social Work, 2012)
Schizophrenia is a mental health condition characterized by broad impairments in cognition that place profound limitations on functional recovery. Social work has an enduring legacy in pioneering the development of novel psychosocial interventions for people with schizophrenia, and in this article the author introduces cognitive remediation, the latest advance in psychosocial treatments for the disorder designed to improve cognition. First, the author presents an overview of the nature of cognitive impairments and their functional consequences in schizophrenia, followed by a description of the theoretical basis and key practice principles of cognitive remediation. Next, the author reviews the latest biopsychosocial evidence for the efficacy of cognitive remediation in schizophrenia. Finally, the author presents a model cognitive remediation program, cognitive enhancement therapy, which was developed and evaluated by a social work-led multidisciplinary team. Cognitive enhancement therapy is a significant advance in cognitive remediation for schizophrenia and uses a unique holistic approach that extends beyond traditional neuro-cognitive training to facilitate the achievement of adult social-cognitive milestones and broader functional recovery. Cognitive remediation is an effective next-generation psycho-social intervention that social workers can use to help improve the lives of many people who live with schizophrenia.